2005
DOI: 10.1063/1.2085027
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of the fast dynamics in glassy polystyrene: First evidence by high-field Electron Paramagnetic Resonance of molecular guests

Abstract: The reorientation of one small paramagnetic molecule (spin probe) in glassy polystyrene (PS) is studied by high-field electron paramagnetic resonance spectroscopy at two different Larmor frequencies (190 and 285 GHz). Two different regimes separated by a crossover region are evidenced. Below 180 K the rotational times are nearly temperature independent with no apparent distribution. In the temperature range of 180-220 K a large increase of the rotational mobility is observed with the widening of the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
50
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 75 publications
7
50
0
Order By: Relevance
“…Buchenau confirmed that conclusion by comparing results from several techniques covering a wide time window from 1Hz up to about 100GHz [18]. The same result has been reached by HF-EPR [10,11,19].…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…Buchenau confirmed that conclusion by comparing results from several techniques covering a wide time window from 1Hz up to about 100GHz [18]. The same result has been reached by HF-EPR [10,11,19].…”
Section: Introductionsupporting
confidence: 69%
“…B 0 ∼ = 3T corresponding to Larmor frequencies about 95GHz ( W band ), [37,38] or even larger frequencies [19,39,40]. HF-EPR is widely used in polymer science [10,11,19,[41][42][43][44]. One major feature is the remarkable orientation resolution [44] due to increased magnitude of the anisotropic Zeeman interaction leading to a wider distribution of resonance frequencies [45].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations